COGNITIVE-LINGUISTIC ANALYSIS OF KINSHIP TERMS IN UZBEK FOLK PROVERBS - Ziyoyeva Marjona Anvar kizi (International Journal of Literature and Language Studies, 2026)
This article investigates the cognitive-linguistic dimensions of kinship terms embedded in Uzbek folk proverbs (paremias). Drawing on conceptual metaphor theory, frame semantics, and cultural script analysis, the study examines how kinship lexemes such as ona (mother), ota (father), aka (elder brother), opa (elder sister), kelin (daughter-in-law), and qaynona (mother-in-law) function not merely as relational designators but as cognitive anchors encoding Uzbek cultural values, social norms, and collective worldview.